2015
DOI: 10.2458/azu_rc.57.18440
|View full text |Cite
|
Sign up to set email alerts
|

Food for Thought: Re-Assessing Mesolithic Diets in the Iron Gates

Abstract: ABSTRACT. Stable isotope ratios of carbon, nitrogen, and sulfur in human bone collagen are used routinely to aid in the reconstruction of ancient diets. Isotopic analysis of human remains from sites in the Iron Gates section of the Lower Danube Valley has led to conflicting interpretations of Mesolithic diets in this key region of southeast Europe. One view (Bonsall et al. 1997(Bonsall et al. , 2004) is that diets were based mainly on riverine resources throughout the Mesolithic. A competing hypothesis (Nehl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
25
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1
1

Relationship

4
5

Authors

Journals

citations
Cited by 21 publications
(29 citation statements)
references
References 25 publications
3
25
1
Order By: Relevance
“…We agree with Bonsall et al (2015) that there is a need for more direct 14 C dates and a larger number of samples to study the dietary preferences at the Iron Gates Gorges in more detail, and a more extensive application of sulfur isotopes on this material is forthcoming by our research group. However, we disagree with the interpretation, especially the quantitative estimations of dietary resources, by Bonsall et al (2015). We have demonstrated here that the dietary input of young animals can be quite substantial and that it cannot be easily dismissed due to a lack of archaeological finds.…”
Section: O Nehlich and D Borićsupporting
confidence: 68%
See 1 more Smart Citation
“…We agree with Bonsall et al (2015) that there is a need for more direct 14 C dates and a larger number of samples to study the dietary preferences at the Iron Gates Gorges in more detail, and a more extensive application of sulfur isotopes on this material is forthcoming by our research group. However, we disagree with the interpretation, especially the quantitative estimations of dietary resources, by Bonsall et al (2015). We have demonstrated here that the dietary input of young animals can be quite substantial and that it cannot be easily dismissed due to a lack of archaeological finds.…”
Section: O Nehlich and D Borićsupporting
confidence: 68%
“…We are fully aware that the data set by Nehlich et al (2010) is far from substantial and comprehensive but may still be representative. While the re-assessment of the chronological order in this region by Bonsall et al (2015) might be more reliable than before, it does not increase the small number of direct radiocarbon dates substantially and therefore is no more precise than before. Additionally, the chronological sorting of the data does not help in any way with the dietary reconstruction despite clear differences in sulfur values between periods that our sample of burials cover, which we explicitly noted in our original study.…”
Section: Responsementioning
confidence: 95%
“…A single Mesolithic level, found towards the entrance of the cave, contained a small lithic assemblage, and is radiocarbon dated to c. 9,800 cal BP (Jovanović et al, 2014). Otherwise, the available documentation is thus mostly confined to the exceptionally rich record of the Iron Gates, where excavations undertaken for several decades have revealed numerous well-preserved sites such as Lepenski Vir, Vlasac and Ogradena-Icoana (see recently Borić et al, 2014;Bonsall et al, 2015a, 2015b, Nehlich and Borić, 2015.…”
Section: Earlymentioning
confidence: 99%
“…Based on a small series of S, N and C measurements on humans, terrestrial mammals and fish, they argued that Iron Gates Mesolithic diets were not uniformly high in aquatic protein. Their data were reinterpreted by Bonsall et al (2015b) to show there was a clear temporal trend in the δ 34 S values, with a matching trend in δ 15 N values, and that the S-isotope data did not necessarily contradict previous interpretations based on C and N isotopes. However, Nehlich et al's research does suggest that S may be a more sensitive indicator of fish consumption among communities living along the Danube, and further research is needed to explain the temporal patterns observed.…”
Section: Dietmentioning
confidence: 83%